The Emerald City of Oz - Shanower, Eric (Marvel, 2014)
The trio from Kansas gets the royal treatment in Oz as they meet living paper dolls, the puzzle-piece Fuddles, and the Spoon Brigade and the whole Kingdom of Utensia! But trouble is brewing: The Nome King is angered that Dorothy stole his magic belt, and he has an army of 50,000 set to invade Oz to get it back! Did Auntie Em and Uncle Henry make it to Oz just in time to see it destroyed?